2016
DOI: 10.3390/ijms17050738
|View full text |Cite
|
Sign up to set email alerts
|

Effect of AQP9 Expression in Androgen-Independent Prostate Cancer Cell PC3

Abstract: It is known that aquaporin 9 (AQP9) in the prostate was strictly upregulated by androgen and may represent a novel therapeutic target for several cancers, but whether AQP9 plays a role in the regulation of androgen-independent prostate cancer still remains unclear. In the present study, AQP9 was determined in prostate cancer and adjacent cancer tissues; AQP9-siRNA was applied to silencing AQP9 in androgen-independent prostate cancer cell PC3 cell line. Western blot and flow cytometry analysis were employed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…However, the mRNA expression of AQP9 is upregulated in breast cancer, and high AQP9 expression may be related to worse relapse-free survival in that disease ( Zhu et al, 2019 ). Chen et al (2016) have demonstrated that the expression of AQP9 is detectable in prostate cancer cells, whereas inhibition of its expression impedes their growth and promotes cell apoptosis through effects on the extracellular regulated protein kinase signaling pathway. AQP9 also functions as an oncogene in astrocytoma by facilitating cell invasion and motility via the AKT pathway ( Lv et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the mRNA expression of AQP9 is upregulated in breast cancer, and high AQP9 expression may be related to worse relapse-free survival in that disease ( Zhu et al, 2019 ). Chen et al (2016) have demonstrated that the expression of AQP9 is detectable in prostate cancer cells, whereas inhibition of its expression impedes their growth and promotes cell apoptosis through effects on the extracellular regulated protein kinase signaling pathway. AQP9 also functions as an oncogene in astrocytoma by facilitating cell invasion and motility via the AKT pathway ( Lv et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increases or decreases in AQP9 expression have been detected in different tumor types. AQP9 is significantly enhanced in prostate cancer tissues than that in adjacent cancer tissues (14); however, AQP9 levels are reduced in human hepatocellular carcinoma compared with the paratumoral normal liver tissues (15). The present study demonstrated that AQP9 was expressed in astrocytoma cells, indicating that AQP9 may be involved in astrocytoma cell progression.…”
Section: Discussionmentioning
confidence: 47%
“…It is reported that AQP9 contributes to cell growth and invasion of prostate cancer cells (14). However, AQP9 can suppress hepatoma cell invasion in vitro and xenograft tumor growth in vivo (16).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that impaired AQP9 expression may contribute to the development of numerous types of cancer, such as lung cancer and malignant brain tumour [16,17]. For instance, the expression of AQP9 in prostate cancer was significantly increased compared with the adjacent tissues [16]. Furthermore, AQP9 could promote the proliferation, migration and invasion, whereas inhibit the apoptosis of prostate cancer cells.…”
Section: Discussionmentioning
confidence: 99%